Anti-HBc IgM associates with acute flare and HBeAg/HBsAg loss in chronic hepatitis B patients with acute exacerbation - Ying Zhang; Ying Zhu; Yi Zhou; Zhaoxia Tan; Yunjie Dan; Xin Zou; Guohong Deng; Wenting Tan (Virulence)
Acute exacerbation (AE) is common for patients with chronic hepatitis B (CHB). The aim of the study is to investigate the values of hepatitis B core antibody (anti-HBc) IgM in CHB-AE. Patients were screened from a prospective sub-cohort, 419 CHB patients with AE were enrolled and divided into groups according to antiviral treatment history, treatment naïve, withdrawal above or within 6 months, and on-treatment. The prevalence, clinical characteristics of anti-HBc IgM, and its relationship with the outcomes of CHB were assessed. A total of 157 patients (37.5%) were tested positive for anti-HBc IgM, of which patients with antiviral-withdrawal more than 6 months had the highest prevalence (49.3%). Anti-HBc IgM was significantly associated with HBV DNA and ALT, regarding to its prevalence and serum level. Furthermore, serum anti-HBc IgM values varied in different phases of CHB, of which immune active and HBeAg-negative chronic hepatitis phases were significantly higher than that in inactive carriers (p = 0.017 and p = 0.0097, respectively). Anti-HBc IgM could distinguish hepatitis from inactive infection phases in HBeAg-negative patients (AUC 0.841). Anti-HBc IgM levels were significantly higher in subgroup who developed ACLF (p < 0.05), but had no relationship with short-term mortality. Finally, anti-HBc IgM seropositivity was the only predictor of HBeAg seroclearance (OR 3.18, 95% CI 1.30–7.73) and all patients who achieved HBsAg seroclearance within 1-year had a markedly elevated anti-HBc IgM level. In conclusion, our study shows anti-HBc IgM is highly prevalent in CHB patients with AE and would be a new predictor of HBeAg and HBsAg loss in this population.